2015
DOI: 10.4103/2249-4863.154659
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-patterns, sleep hygiene behaviors and parental monitoring among Bahrain-based Indian adolescents

Abstract: Introduction:Sleep plays an important role in adolescent's health and undergoes substantial changes with puberty and physical maturation with a preference for later bed times. Evidence shows that many adolescents are not obtaining the required amounts of sleep which is 9.25 h, due to inadequate sleep practices, academic and societal demands. This study aims at describing the (1) sleep patterns of adolescents on school days and weekends, (2) sleep hygiene practices and the extent of parental monitoring and (3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 32 publications
1
12
2
Order By: Relevance
“…In our study, sleep duration was not significantly associated with age or grade. The finding is not consistent with a study done by John in 2015 this previous study [10] . However, this finding is consistent with Yang et al [16] as it is stated that the transition point for changes in sleep duration occurs in the 10th grade as all higher grades (10th, 11th, and 12th) have the same academic demand and our study included those three grades only.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…In our study, sleep duration was not significantly associated with age or grade. The finding is not consistent with a study done by John in 2015 this previous study [10] . However, this finding is consistent with Yang et al [16] as it is stated that the transition point for changes in sleep duration occurs in the 10th grade as all higher grades (10th, 11th, and 12th) have the same academic demand and our study included those three grades only.…”
Section: Discussioncontrasting
confidence: 96%
“…Our questionnaire was adopted and modified from previous studies [8] , [10] . The questionnaire, consisted of 4 sections: i) demographic data; ii) sleep patterns of adolescents; iii) sleep problems including (difficulty falling asleep, frequent arousals with difficulty getting back to sleep, early morning awakenings with inability to fall back to sleep again and non-restoring sleep) all of those problems are used to assess for insomnia [7] ; iv) lifestyle habits including physical activity, smoking and use of electrical devices (TV, computer, tablet, or mobile phones) before sleep.…”
Section: Methodsmentioning
confidence: 99%
“…• Evidence showed that good sleep hygiene (e.g., regular bedtimes, read at bedtime, or fall asleep in bed) was positively associated with sleep duration [160][161][162][163][164][165][166], sleep quality [167], and negatively associated with sleep latency (the amount of time it takes to go from being fully awake to sleeping) [168]. • Implementing consistent bedtime routines (e.g., bath, massage, brushing teeth, and quiet activities) has been shown to be beneficial for sleep onset latency, frequency and duration of nighttime awakenings, and sleep consolidation [169].…”
Section: Evidence From the Canadian Health Measures Survey (Chms)mentioning
confidence: 99%
“…Adolescence is a critical period which marks puberty and physical maturation, where there is a gradual transition between childhood and adulthood. [1] Sleep affects physical, mental, and emotional development of the adolescents, and it has a potential impact on their academic performance. [2] Adolescents should sleep 8–10 h/day on a regular basis to promote optimal health.…”
Section: Introductionmentioning
confidence: 99%